Profiling wines in China for the biogenic amines: A nationwide survey and pharmacokinetic fate modelling. (1st June 2018) - Ke, Runhui; Wei, Zongsu; Bogdal, Christian; Göktaş, Recep Kaya; Xiao, Ruiyang
Highlights: We conducted a nationwide survey of Chinese wines for the occurrence of biogenic amines (BAs). Sampling campaign covered >90% of wine ( n = 456) in China from 2014 to 2016. Different exposure scenarios were simulated with PBPK model to characterize risk. The study provided baseline for risk assessment for BAs dietary uptake. Abstract: Biogenic amines (BAs), a class of nitrogenous compounds that are frequently detected in wine, pose adverse effects to humans. However, with the largest red wine consumption in the world, little is known about national profiles correlating BAs in wines to toxicological/health risks in China. In this study, we conducted a nationwide survey of commercially available wines for the occurrence of BAs. Our sampling campaign covered >90% of wine brands ( n = 456) in China in a three year span (2014–2016). The target BAs included tryptamine, phenylethylamine, putrescine, cadaverine, histamine, tyramine, spermidine and spermine. In order to quantitatively characterize the potential risk and/or support regulatory decision-making, chronic and acute BA exposure scenarios were developed and simulated with a physiologically based pharmacokinetic model. The model described the fate and transport of BAs within human body using physical descriptions of relevant processes. These results provided baseline data that are needed for the risk assessment of dietary uptake of BAs and evaluating winemaking processes by food safety authorities.